ANTIBACTERIA ACTIVITY OF GASTROPOD ASSOCIATION BACTERIA FROM MANGROVE ECOSYSTEM AGAINST BACILLUS CEREUS AND ESCHERICHIA COLI AND IT’S POTENCY OF APPLICATION FOR BELANAK FISH (MUGIL SUBVIRIDIS) - Patria Ami Wijaya; Delianis Pringgenies; Ervia Yudiati (JFMR (Journal of Fisheries and Marine Research), 2021)
Gastropod association bacteria from magrove ecosystem have a great potency as antibacteria. The contamination of Escherichia coli and Bacillus cereus can cause damage in fish product. The aims of these research are to determine gastropod association bacteria that can inhibit E. coli and B. cereus growth, as well as the contaminantion bacteria in Belanak (Mugil subviridis). Gastropods sample Certhideopsilla alata, Cerithidea quoyii, Cassidula aurisfelis, Cassidula nucleus, Telescopium telescopium were collected at Mangrove Education Park, Tugu, Semarang. The resaerch procedure were isolation, antibacteria test, biochemistrically identification, and then application in Belanak fish (Mugil subviridis). There were 61 bacteria isolated. Thirteen isolates were able to inhibit E. coli and eight to B. cereus. Supernatant of GMT 3.2.5 and GMT 4.1.3 have the most widely inhibition zone, (8,48 mm and 7,84 mm). Biochemistry identification shown that GMT 3.2.5 and GMT 4.1.3 has identic characteristic with genus Micrococcus sp. and Bacillus sp. Total plate count (cfu/ml) of bacteria from Belanak fish flesh that soaked by Micrococcus sp. GMT 3.2.5 and Bacillus sp. GMT 4.1.3 supernatant were 115 x 104 and 265 x 103colony. The colony were less than negative control (2312 x 103 colony). The association bacteria can inhibit contaminant bacteria in Belanak fish.